2014
DOI: 10.1016/j.cct.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and study protocol for the ‘Active Teen Leaders Avoiding Screen-time’ (ATLAS) group randomized controlled trial: An obesity prevention intervention for adolescent boys from schools in low-income communities

Abstract: ATLAS is an innovative school-based intervention designed to improve the health behaviors and related outcomes of adolescent males in low-income communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 94 publications
1
69
0
1
Order By: Relevance
“…Intervention effects for the primary and secondary outcomes were examined by using linear mixed models adjusted for school clustering and participant socioeconomic status, and all analyses followed the intention-to-treat principle. 36 Prespecified subgroup analyses 21 for all body composition outcomes were conducted for those classified as overweight/obese (combined as a single group) at baseline. In addition, the proportional difference between treatment groups among those improving their weight status (ie, moving from "obese" to "overweight" or from "overweight" to "healthy weight") or regressing to a poorer weight status (ie, moving from "healthy weight" to "overweight" or from "overweight" to "obese") was explored by using Pearson' s x 2 test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention effects for the primary and secondary outcomes were examined by using linear mixed models adjusted for school clustering and participant socioeconomic status, and all analyses followed the intention-to-treat principle. 36 Prespecified subgroup analyses 21 for all body composition outcomes were conducted for those classified as overweight/obese (combined as a single group) at baseline. In addition, the proportional difference between treatment groups among those improving their weight status (ie, moving from "obese" to "overweight" or from "overweight" to "healthy weight") or regressing to a poorer weight status (ie, moving from "healthy weight" to "overweight" or from "overweight" to "obese") was explored by using Pearson' s x 2 test.…”
Section: Discussionmentioning
confidence: 99%
“…20 The rationale and study protocols have been reported previously. 21 Briefly, ATLAS was evaluated by using a cluster randomized controlled trial conducted in state-funded coeducational secondary schools within low-income areas of New South Wales, Australia. The SocioEconomic Indexes For Areas (SEIFA) of relative socioeconomic disadvantage (scale: 1 = lowest to 10 = highest) was used to identify eligible schools.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 4818 titles identified from the database search, 64 articles were included: 9 reporting dietary self-monitoring trials (38)(39)(40)(41)(42)(43)(44)(45)(46), 18 reporting nutritionimprovement trials (36,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), 30 reporting applicationdevelopment projects (37,, and 7 reporting qualitative studies with consumers (93)(94)(95)(96)(97)(98)(99). Five reports were published in 2016, 16 each in 2015 and 2014, 11 in 2013, and 16 between 2008 and 2012.…”
Section: Overviewmentioning
confidence: 99%
“…Theoretically, based-interventions are more effective in changing behavior than non-theoretical approaches [1][2][3][4] . Bandura's SCT 5 is a useful framework for explaining why people acquire and maintain health behaviors, as well as to hypothesize that a behavior change is influenced by a complex interaction referred to as "reciprocal determinism", which occurs between personal factors, environmental factors, and factors influenced by the other's behavior 5,6 .…”
Section: Introductionmentioning
confidence: 99%